Antagonism of human formyl peptide receptor 1 with natural compounds and their synthetic derivatives; International Immunopharmacology; Vol. 37 - Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Khlebnikov A. I. Andrey Ivanovich; Kirpotina L. N. Liliya Nikolaevna; Quinn M. T. (2016, 2016)
Title screen